Students’ Readiness for Online and Distance Education at the Nueva Vizcaya State University - Ramel, Micah Ryan B. (International Journal on Open and Distance e-Learning, 2020)
Utilizing quantitative research through the survey method as the means of gathering data, this study harnessed a researcher-developed questionnaire to draw the responses of 38 graduating students from the Accountancy, Business and Management Track of the Nueva Vizcaya State University College of Teacher Education Senior High School program, to assess their readiness for online and distance education. Results showed that the graduating students from the SHS ABM Track have favorable overall attitudes towards e-learning and are ready for online and distance education. Moreover, the students are competent in the use of offline computer-based technologies, are competent in the use of mobile-based technologies, and are competent in the use of Internet-based technologies. The results manifest the following: (1) there is a very significant and positive correlation between students’ activities in computer-based technologies (offline) and their attitudes towards learning; (2) there is a significant and positive correlation between students’ mobile Internet activity and their attitudes towards e-learning; and, (3) a very significant and positive correlation between the students’ Internet-based activities and their attitudes towards elearning. Based on the strengths of the results, recommendations on how the University may be able to strengthen its ODE capability and to respond to the needs of prospective students were placed forward for consideration by the administration.